Anti-ferroptotic properties of isolates from traditional South African medicinal plants in a 6-hydroxydopamine-induced SH-SY5Y cytotoxicity model - Cordier, Werner (University of Pretoria, 2025)
Thesis (PhD (Pharmacology))--University of Pretoria, 2024.